A meta-analysis comparing stereotactic body radiotherapy vs conventional radiotherapy in inoperable stage I non-small cell lung cancer. Issue 34 (21st August 2020) - Li, Can; Wang, Li; Wu, Qian; Zhao, Jiani; Yi, Fengming; Xu, Jianjun; Wei, Yiping; Zhang, Wenxiong
Abstract: Background: Stereotactic body radiotherapy (SBRT) superseded conventional radiotherapy (CRT) for the treatment of patients with inoperable early stage non-small cell lung cancer (NSCLC) over a decade ago. However, the direct comparisons of the outcomes of SBRT and CRT remain controversial. This meta-analysis was performed to compare the survival and safety of SBRT and CRT in patients with inoperable stage I NSCLC. Methods: We systematically searched the Cochrane Library, Embase, PubMed, Web of Science, Ovid MEDLINE, ScienceDirect, Scopus and Google Scholar for relevant articles. Overall survival (OS), progression-free survival (PFS), lung cancer-specific survival (LCSS), local control rate (LCR) and adverse effects (AEs) were the primary outcomes. Results: We identified 11, 110 articles, 17 of which were eventually included in this study; these 17 articles had 17, 973 patients (SBRT: 7395; CRT: 10, 578). Compared to CRT for the treatment of inoperable stage I NSCLC, SBRT had superior survival in terms of OS (hazard ratio [HR]: 0.66, 95% confidence interval [CI]: 0.62-0.70, P < .00001), LCSS (HR: 0.42 [0.35-0.50], P < .00001), and PFS (HR: 0.34 [0.25-0.48], P < .00001). The 4-year OS rate (OSR); 4-year LCSS rate (LCSSR); 3-year local control rate (LCR); 5-year PFS rate (PFSR) with SBRT were all higher than those with CRT. With regard to all-grade AEs, the SBRT group had a significantly lower rate of dyspnea, esophagitis and radiation pneumonitis; no significant difference was found in grade 3-5 AEs (risk ratio [RR]: 0.68 [0.30-1.53], P = .35). Conclusions: With better survival and a lower rate of dyspnea, esophagitis and radiation pneumonitis than CRT, SBRT appears to be more suitable for patients with inoperable stage I NSCLC. Abstract : Supplemental Digital Content is available in the text